On the molecular genetics of hereditary degenerative retinopathies - Aherne, Aileen Mary (Trinity College (Dublin, Ireland). Department of Genetics, 2004)
The central aim of this thesis was the elucidation of the underlying molecular pathologies of inherited diseases of the retina. The main focus of study concentrates on the molecular genetics and disease mechanisms in retinitis pigmentosa (RP), a hereditary disease in which photoreceptor cells of the retina degenerate, eventually leading to blindness in affected individuals.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin